Focality and Extension in Kinship Essays in Memory of Harold W. Scheffler - Shapiro, Warren (ANU Press, 2018)
When we think of kinship, we usually think of ties between people based upon blood or marriage. But we also have other ways-nowadays called 'performative'-of establishing kinship, or hinting at kinship: many Christians have, in addition to parents, godparents; members of a trade union may refer to each other as 'brother' or 'sister'. Similar performative ties are even more common among the so-called 'tribal' peoples that anthropologists have studied and, especially in recent years, they have received considerable attention from scholars in this field. However, these scholars tend to argue that performative kinship in the Tribal World is semantically on a par with kinship established through procreation and marriage. Harold Scheffler, long-time Professor of Anthropology at Yale University, has argued, by contrast, that procreative ties are everywhere semantically central, i.e. focal, that they provide bases from which other kinship ties are extended. Most of the essays in this volume illustrate the validity of Scheffler's position, though two contest it, and one exemplifies the soundness of a similarly universalistic stance in gender behaviour. This book will be of interest to everyone concerned with current controversy in kinship and gender studies, as well as those who would know what anthropologists have to say about human nature.